Ferns Species Diversity in the Sekar Pudak Sari Waterfall Tourism Area, Wonosalam District, Jombang Regency, East Java, Indonesia - Puspita , Bintan Felia; Wisanti, Wisanti (Universitas Negeri Surabaya, 2023)
Ferns are significantly dominant in Indonesia. The waterfall area is one of the ferns habitats. This study aims to determine the diversity index of ferns species in the Tourism Area of Sekar Pudak Sari Waterfall Wonosalam District, Jombang Regency, East Java. This research was exploratory, descriptive. Data collection uses a single plot measuring 20x20 m at 500 masl, 700 masl, and 900 masl. Each observation plot has a sub-plot with a size of 2x2 m. Data analysis used the Shannon-Wiener diversity index (H'), the taxonomic diversity index (?), and dominance (?*). The exploration results found 28 species from 11 families, 6 epiphytes, and the rest terrestrial. The taxonomic diversity index in plot 1 was 23.36 (low category), while plots 2 and 3 were 30.58 and 31.66 (medium category). This shows that the environment in the three plots is classified as stable, as indicated by the presence of ferns at various taxonomic levels. The highest dominance diversity index (?*) was 2.8 in Plot 2, while Plots 1 and 3 were 2.7 (low category). The total number of individual ferns found influenced the difference in the diversity index. The ferns found in the three plots were relatively few, indicating that the environment was classified as less stable. The Shannon-Wiener diversity index (H') in the three plots was 2.9 (medium category), indicating that the distribution pattern of ferns in the environment was balanced. The Sekar Pudak Sari Waterfall Tourism Area is a suitable habitat for the growth of ferns, so conservation efforts need to be made to maintain a balance of species and stabilize the ecosystem.